Development of Moodle-based Learning Media using Blended Learning Methods in Graphic Design Subject - Arif Setiawan; Dimas Radika Putra; Sujalwo Sujalwo; Aditya Nur Cahyo (Faculty of Science and Technology, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
This research aims to develop learning media using Moodle and apply blended learning methods to help improve the learning effectiveness of students at SMK Muhammadiyah 1 Klaten. The research method used in this research is Research and Development. The results showed the average value of media experts was 79.55% categorized as feasible category, while the material experts were 75% categorized as feasible category. Whereas the System Usability Scale (SUS) questionnaire, which could measure usability, from 32 students of SMK Muhammadiyah 1 Klaten consist of 29 Male and 3 Female Students obtained 71.25% which were categorized as acceptable category. The average test results of the students' pre-test scores were 58.75%, the post-test scores were 81.87%, an increase of 23.12%. The conclusion in this study is that learning media using Moodle-based blended learning methods are appropriate for use in basic graphic design subjects, and are effectively used to improve student understanding and learning outcomes.